Position Papers from The 7th Workshop for PhD Students in Object-Oriented Systems - Gerhardt, Frank; Wohlrab, Lutz; Ernst, Erik (DAIMI Report Series, 1997)
DAIMI-PB 526 contains the position papers accepted at The 7th Workshop for PhD Students in Object-Oriented Systems, which took place June 9-10, 1997, in Jyväskylä, Finland, in connection with the ECOOP'97 conference. There were 36 participants, and many areas of research were represented since the technical topics covered were derived from the research interests of the participants. Hence, the report can be used to obtain an overview of the work being done by young researchers in the area of object orientation right now. The individual papers can be found at http://www.daimi.au.dk/~eernst/ws97/papers.html